A pilot study of alterations of the gut microbiome in canine chronic kidney disease - Kim, Kyung-Ryung; Kim, Seon-Myung; Kim, Jung-Hyun (Frontiers in Veterinary Science, 2023)
Introduction: Gut dysbiosis has been noted in humans and animals with chronic kidney disease (CKD). However, little is known about the gut microbiome in canine patients with CKD. This study aimed to analyze and compare the gut microbiome profiles of healthy and CKD dogs, including differences in the gut microbiome between each CKD stage. Methods:The study was conducted on 29 client-owned dogs who underwent physical examination, complete blood count (CBC), serum biochemistry, and urinalysis. The gut microbiome profile of healthy dogs (n = 10) and dogs with CKD (n = 19) was analyzed employing 16S rRNA sequencing. Results: Significant differences were seen in the composition of the gut microbiome, with increased operational taxonomic units from the phylum Proteobacteria (P = 0.035), family Enterobacteriaceae (P < 0.001), and genus Enterococcus (P = 0.002) in dogs with CKD, and a decrease in the genus Ruminococcus (P = 0.007). Furthermore, an increase in both the progression of CKD and abundance of genus Klebsiella (Jonckheere-Terpstra test statistic value (JT) = 2.852, P = 0.004) and Clostridium (JT = 2.018, P = 0.044) was observed. Discussion: Our study demonstrated that in dogs with CKD, the composition of the gut microbiome varied depending on the stage of CKD. Alterations in gut microbiome composition observed in CKD patients are characterized by an increase in proteolytic bacteria and a decrease in saccharolytic bacteria. These findings suggest specific gut microbiota could be targeted for clinical management of uremic dogs with CKD.